Uptake of intermittent preventive treatment for malaria during pregnancy with Sulphadoxine-Pyrimethamine in Malawi after adoption of updated World Health Organization policy: an analysis of demographic and health survey 2015-2016 - Steven Chifundo Azizi (BMC, 2020)
Abstract Background Malawi adopted the 2012 updated Word Health Organization (WHO) Intermittent preventive treatment of malaria during pregnancy with sulphadoxine-pyrimethamine (IPTp-SP) policy in 2013. This study aimed to estimate the proportion of and identify factors associated with the uptake of at least three doses of IPTp with SP among pregnant women in Malawi after the adoption and operationalisation of updated WHO IPTp-SP policy. Methods The 2015-16 Malawi Demographic and Health Survey dataset was analysed. Of 1219 women aged 15-49 years who had live births and the children were born after the date of July 2015, 1069 women were included in the analysis. Bivariate and multiple logistic regression were used in data analysis. The statistical analysis took into account a complex survey sample design. Results Of the 1069 women, 447 (42, 95% CI: 38.1-45.6) received three (optimal) or more doses of IPTp-SP. Less than half (47%) managed to attend at least four antenatal care (ANC) clinics. Only 52% received optimal SP doses among those who made at least four ANC visits. Only the number of ANC visits was associated with the optimal uptake of SP. Women who attended ANC three times only and those who visited ANC once or twice only were less likely to receive at least three doses of SP than those who managed to attend ANC at least four times during pregnancy (AOR = 0.71, 95% CI 0.49-1.02) and (AOR = 0.12, 95% CI 0.06-0.21) respectively. Conclusions To achieve effective malaria prevention in pregnancy, IPTP-SP is used alongside other interventions. However, there is low uptake of optimal SP doses in Malawi, and this seems to be associated with the number of ANC visits. Moreover, there is limited effectiveness of an increased number of ANC visits on the uptake of optimal SP doses. Further research should be done to explore health systems factors affecting uptake of optimal IPTp with SP doses during pregnancy.